Faculty supporting and developing a CBE program – strategies implemented at the University of Mary Hardin‐Baylor. Issue 1 (April 2016) - Cooper, Tammi R.
Abstract : Faculty play key roles in developing and supporting academic programs. For traditional modes of delivery, the ways faculty support and develop academic offerings are well‐defined and understood. However, for new modes of delivery like CBE, successful faculty support will only occur through the use of intentional strategies aimed at inspiring support and encouraging lasting involvement. This article examines how campus leaders at the University of Mary Hardin‐Baylor engaged traditional faculty members during the development of a fully online undergraduate competency‐based program. Strategies used to initially garner faculty support, to provide new leadership opportunities to faculty, and to systematically involve faculty throughout the curriculum development process and beyond are presented.